Implementation of algorithm C4-5 on the number of children acquiring birth certificates in Office of Population and Civil Registry Palembang City - Wulan Damayanti; Devi Udariansyah (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
The aim of this study is to utilize the C4.5 algorithm in data mining to classify child certificates that are registered and unregistered. Additionally, decision trees will be employed to determine the gain associated with each attribute. The implementation of the C4.5 algorithm will be facilitated by the utilization of RapidMiner 9.5 software. The initial step in the research process is gathering aggregate data pertaining to the recipients of deeds in Office of Population and Civil Registry Palembang City throughout the time frame of 2021 to 2023. Subsequently, the data is subjected to analysis with the use of Microsoft Excel and RapidMiner 9.5 in order to ascertain the entropy value, gain value, and decision tree. The findings indicated that a total of 1,606 individuals were identified as True Positive (TP), representing Palembang City residents who had successfully registered at Office of Population and Civil Registry Palembang City. Additionally, there were 397 records classified as False Negative (FN), indicating the number of individuals who have yet to register themselves on the birth certificate of Office of Population and Civil Registry Palembang City.